Pharmacokinetics And Pharmacodynamics Of Azithromycin In Severe Malaria Bacterial Co-Infection In African Children (TABS-PKPD): A Protocol For A Phase II Randomised Controlled Trial - Olupot, Peter Olupot; Okiror, William; Mnjalla, Hellen; Muhindo, Rita; Uyoga, Sophie; Mpoya, Ayub; Williams, Thomas N.; terHeine, Rob; Burger, David M.; Urban, Britta; Connon, Roisin; George, Elizabeth C.; et al. (Wellcome Open Research, 2021)
African children with severe malaria are susceptible to Gram-negative bacterial co-infection, largely non-typhoidal Salmonellae, leading to a substantially higher rates of in-hospital and post-discharge mortality than those without bacteraemia. Current evidence for treating co-infection is lacking, and there is no consensus on the dosage or length of treatment required. We therefore aimed to establish the appropriate dose of oral dispersible azithromycin as an antimicrobial treatment for children with severe malaria and to investigate whether antibiotics can be targeted to those at greatest risk of bacterial co-infection using clinical criteria alone or in combination with rapid diagnostic biomarker tests. A Phase I/II open-label trial comparing three doses of azithromycin: 10, 15 and 20 mg/kg spanning the lowest to highest mg/kg doses previously demonstrated to be equally effective as parenteral treatment for other salmonellae infection. Children with the highest risk of bacterial infection will receive five days of azithromycin and followed for 90 days. We will generate relevant pharmacokinetic data by sparse sampling during dosing intervals. We will use population pharmacokinetic modelling to determine the optimal azithromycin dose in severe malaria and investigate azithromycin exposure to change in C-reactive protein, a putative marker of sepsis at 72 hours, and microbiological cure (seven-day), alone and as a composite with seven-day survival. We will also evaluate whether a combination of clinical, point-of-care diagnostic tests, and/or biomarkers can accurately identify the sub-group of severe malaria with culture-proven bacteraemia by comparison with a control cohort of children hospitalized with severe malaria at low risk of bacterial co-infection.
Keywords: Severe Malaria, Bacterial infection, African Children, Antibiotics, azithromycin, Clinical Trial, Pharmacokinetics, Pharmacodynamics, Biomarkers